2023
DOI: 10.1021/acs.jmedchem.2c02073
|View full text |Cite
|
Sign up to set email alerts
|

New Long-Acting [89Zr]Zr-DFO GLP-1 PET Tracers with Increased Molar Activity and Reduced Kidney Accumulation

Abstract: Positron emission tomography (PET) imaging is used in drug development to noninvasively measure biodistribution and receptor occupancy. Ideally, PET tracers retain target binding and biodistribution properties of the investigated drug. Previously, we developed a zirconium-89 PET tracer based on a long-circulating glucagon-like peptide 1 receptor agonist (GLP-1RA) using desferrioxamine (DFO) as a chelator. Here, we aimed to develop an improved zirconium-89-labeled GLP-1RA with increased molar activity to increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 71 publications
(126 reference statements)
0
2
0
Order By: Relevance
“…This research utilized a cleavable linker which could be recognized and cleaved by angiotensin-converting enzyme (ACE) or neprilysin to reduce kidney uptake of radio­labeled peptides and proteins. , Gustafsson et al describe the in vitro and in vivo evaluation of new long-lasting glucagon-like peptide 1 (GLP-1) derivatives labeled with Zr-89. Reduced kidney accumulation was achieved by introducing an enzymatically cleavable motif between the chelator and the peptide …”
Section: Radiopharmaceuticals For Cancer Imaging and Therapymentioning
confidence: 99%
“…This research utilized a cleavable linker which could be recognized and cleaved by angiotensin-converting enzyme (ACE) or neprilysin to reduce kidney uptake of radio­labeled peptides and proteins. , Gustafsson et al describe the in vitro and in vivo evaluation of new long-lasting glucagon-like peptide 1 (GLP-1) derivatives labeled with Zr-89. Reduced kidney accumulation was achieved by introducing an enzymatically cleavable motif between the chelator and the peptide …”
Section: Radiopharmaceuticals For Cancer Imaging and Therapymentioning
confidence: 99%
“…Reduced kidney accumulation was achieved by introducing an enzymatically cleavable motif between the chelator and the peptide. 30 The work of Sutcliffe et al combines the integrin α v β 6 binding peptide (α v β 6 -BP) with the cytotoxic agent monomethyl auristatin E (MMAE) with the goal to increase efficacy while reducing peripheral toxicity. This peptide−drug conjugate (PDC) was designed to contain a metal chelator (DOTA), enabling radiolabeling with PET radionuclides, thus demonstrating utility as a theranostic, and a protease-cleavable linker which is hydrolyzed by an enzyme that is upregulated in cancer cells, resulting in the release of MMAE.…”
Section: Imaging and Therapymentioning
confidence: 99%
“…But, for example, for drugs acting in the central nervous system, the exposure at the target site may differ from plasma, because their distribution is dependent on the functionality of specific transporters due to the presence of the blood brain barrier. 44 For SGLT2 inhibiters, the target site is the proximal tubule in the kidney, where they bind to the SGLT2, most likely from the luminal side. 45 ARBs target the angiotensin II type 1 receptor (AT 1 R), in kidneys expressed in the glomeruli, proximal and distal tubules, and afferent and efferent arterioles.…”
Section: Pharmacodynamic Factorsmentioning
confidence: 99%
“…Blood oxygenation level-dependent MRI (BOLD-MRI) uses the difference in magnetic properties of oxygenated versus deoxygenated hemoglobin. 44 Method validation has been performed in pig and the reproducibility has been assessed in healthy volunteers and patients with CKD. 24,[45][46][47] The first BOLD-MRI studies evaluating renal oxygenation showed conflicting results.…”
Section: Renal Oxygenation Blood Oxygenation Level-dependent Mrimentioning
confidence: 99%
See 1 more Smart Citation